Ascertaining the Educational Efficacy of using Free Open-source Software Research Artificial Intelligence Tools: A Formulative Study at CPGS-AS, CAU(I), Umiam, Ri-Bhoi, Meghalaya - , Pankaj Kumar; , R. J. Singh; , L. Devarani; , Th Onchoila Maring (Archives of Current Research International, 2025)
One of the most significant challenges students currently face is the task of writing and publishing research papers. This process requires a systematic and distinctive approach, including comprehensive analysis, critical interpretation, and the ability to synthesize research on a specific topic. In the current academic and professional landscape, proficiency in artificial intelligence (AI) has become an essential prerequisite for students to excel in this domain. Although artificial intelligence (AI) has become increasingly important in academic research, there remains a paucity of studies exploring its application and impact. Therefore, the present study was conducted to examine the awareness and ascertain the efficacy of using Free and Open-Source Software (FOSS) AI tools in academic research among M.Sc. (Ag.) students at CPGS-AS, CAU (I), Umiam, Ri-Bhoi, Meghalaya. The study adopted a formative research design to achieve its objectives. Convenient sampling procedure was carried out in order to select 62 respondents. The scientific inquiry revealed that the majority of respondent (67.74%) were aware of Software Ownership; while 75.80% were knowledgeable about the features of FOSS, particularly its freedom to use FOSS AI tools. Additionally, more than half of the respondents (67.2%) reported learning about FOSS AI tools through social media and the internet. However, majority of respondents (79.03%) demonstrated low awareness of the use of FOSS AI tools in academic research. A statistically significant difference was found in the respondents' scores before and after the intervention of FOSS AI tools in academic research, indicating a marked improvement in efficacy among the students.